(untitled) (JURNAL HUKUM DAS SOLLEN, 2022)
This article examines the validity of the settlement of insurance claims through ex-gratia. Settlement of insurance claims through non-litigation, namely by negotiation, mediation through the Indonesian Insurance Mediation and Arbitration Agency (BMAI), Adjudication and Arbitration. However, recently, many insurance companies have begun to settle claims using ex gratia agreements. In Law Number 40 of 214 concerning Insurance there is no article that describes ex gratia as one of the settlements of the insurance agreement settlement. Likewise, in Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, there are no clear provisions. For this reason, through this research, the legal validity of the use of ex gratia will be disclosed and analyzed as a vehicle for the settlement of insurance agreements. Keywords: Validity, Insurance Agreement Claims, Ex Gratia and Legal Certainty